Mr Tompkins Learns the Facts of Life - George Gamow (Cambridge University Press, 2011)
George Gamow\'s first Tompkins book, Mr Tompkins in Wonderland, created a \'toy universe\' where, as his son comments in the preface to this 2010 reprint, \'the maximum speed of light is assumed to be 10 miles per hour, while all the laws of general relativity still hold\'. Since the death of the author in 1968, the Mr Tompkins series has gone through a number of reincarnations. The latest reincarnation, The Adventures of Mr Tompkins (www.theadventuresofmrtompkins.com), has Mr Tompkins not only visiting physicists, well also one biologist in Mr Tompkins Learns the Facts of Life but he also visits a slew of scientists from all branches of science and mathematics, from their very beginnings to the present time, from Aristotle to Watson and Crick.